FREEZE DRYING OF FISHERY PRODUCTS:PART IV -BIOCHEMICAL CHANGES OCCURRING IN PRAWN MUSCLE DURING FREEZING,FREEZE DRYING AND PROLONGED STORAGE OF THE FREEZE DRIED PRODUCT. - GOVINDAN, T K (Fishery Technology, 2017)
The changes occurring in water and sa1t extractable protein and non-protein fractions in prawn muscle of different species during freezing, freeze drying and subsequent prolonged storage have been studied. There is no denaturation of water extractable proteins, whereas salt extractable proteins wen rendered insoluble to the extent of 21% due to freeze drying. The freeze dried products remained in good edible condition for 32 months of storage up to which sto1age characteristics were followed.